Length-Weight Relationship and Condition Factor of Tillapia zilli in River Yobe, Northeast, Nigeria - Samuel Segun Ashley-Dejo; Ijabo Samuel Ogah; Yahya Usman (Jurnal Perikanan Universitas Gadjah Mada, 2022)
This study examined the length-weight relation and condition factor of Tillapia zilli in River Yobe, Northeast, Nigeria. Three hundred fifty fish species were collected from commercial fishers at selected landing sites within the study area between June and November 2020. The morphometric and meristic characteristics examined varies due to environmental variations such as water temperature, stress, food availability, spawning ground, fishing intensity, and sex. The mean condition factor shows no significant difference (P < 0.05) throughout the sampling period. A linear relationship was established W = 0.4667 L1.1279 and significant at P < 0.01 with b value indicating a negative allometric growth pattern. The correlation coefficient (r2 = 0.5212) indicated that LWR model is reliable. This study provides baselines on length-weight relation and condition factor of Tillapia zilli in River Yobe. Thus further research should be encouraged on the water body for sustainable utilization, decision making, and policy formulation.